A Decision Support System for the Selection of Outstanding Students Using the SAW (Simple Additive Weighting) Method at SMA Negeri 1 Padang - Nabil Nazran Harianto; Airin Mai Winata; Lela Budiarti (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2026)
The selection of outstanding students is an important process in educational institutions to recognize academic and non-academic achievements. However, the process is often carried out subjectively and lacks a systematic approach, which can lead to less accurate and inconsistent results. This study aims to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to assist in selecting outstanding students at SMA Negeri 1 Padang. The SAW method is applied to evaluate multiple criteria, including academic performance, extracurricular activities, attendance, behavior, and achievements. Each criterion is assigned a weight based on its level of importance, and the alternatives (students) are ranked according to the final score obtained from the SAW calculation. The results of this study indicate that the proposed system is capable of providing objective, transparent, and efficient recommendations in determining outstanding students. The implementation of the DSS is expected to support decision-makers in producing fair and accurate selections